2001
DOI: 10.1128/aem.67.9.4186-4191.2001
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Clinical and Poultry-Derived Isolates of Campylobacter jejuni at a Low Temperature (4°C)

Abstract: Campylobacter jejuni is a leading cause of bacterial gastroenteritis in humans, and contamination of poultry has been implicated in illness. The bacteria are fastidious in terms of their temperature requirements, being unable to grow below ca. 31°C, but have been found to be physiologically active at lower temperatures and to tolerate exposure to low temperatures in a strain-dependent manner. In this study, 19 field isolates of C. jejuni (10 of clinical and 9 of poultry origin) were studied for their ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 31 publications
7
75
3
Order By: Relevance
“…The results showed that there was a reduction of 1 or 2 log 10 CFU on Campylobacter counts for skin stored at 4ºC or -20ºC, respectively. This reduction was lower than the value normally reported for Campylobacter cells stored at -20ºC (3 log 10 CFU) (Chan et al, 2001), which indicates that chicken skin may have had a protective effect. Phage φ2 at 10 7 PFU was added to chicken skin samples and was show to survive for ten days at 4ºC and at -20 ºC.…”
Section: Campylobactercontrasting
confidence: 49%
“…The results showed that there was a reduction of 1 or 2 log 10 CFU on Campylobacter counts for skin stored at 4ºC or -20ºC, respectively. This reduction was lower than the value normally reported for Campylobacter cells stored at -20ºC (3 log 10 CFU) (Chan et al, 2001), which indicates that chicken skin may have had a protective effect. Phage φ2 at 10 7 PFU was added to chicken skin samples and was show to survive for ten days at 4ºC and at -20 ºC.…”
Section: Campylobactercontrasting
confidence: 49%
“…weeks (Chan et al, 2001) to more than 4 months (Rollins and Colwell, 1986;Cools et al, 2003). These differences were supposed to be attributed to strain variations, differences in experimental conditions or in the methodology of culturability assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Although not able to grow below 30°C, C. jejuni is able to survive at refrigerated temperatures (40). It was already shown that the exoribonuclease polynucleotide phosphorylase was important for the survival at refrigerated temperatures (9).…”
mentioning
confidence: 99%